2018
DOI: 10.1186/s41018-018-0029-4
|View full text |Cite
|
Sign up to set email alerts
|

Practices and consequences of using humanitarian technologies in volatile aid settings

Abstract: This article presents the results of an exploratory study into aid agencies' use of technologies for security purposes. Since there appears to be a consensus in the aid sector that areas of operations are increasingly dangerous, aid agencies are upgrading their security strategies by adopting technological innovations. I conducted Skype interviews with security managers and country directors responsible for operations in dangerous countries. These interviews show that humanitarian technologies are more and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…(Soesilo et al, 2019(Soesilo et al, & 2016, and the use of UAV drones in humanitarian action is a rapidly emerging field (Dowson, 2018;Tasevski, 2018). Kalkman (2018) carried out exploratory research into humanitarian aid agencies' use of technologies during post-crisis rehabilitation and found that the use of IT had significantly increased in these areas. It was concluded that technology must not be treated as a neutral fix since it can leave political aftermath if used incorrectly (Raghad and Dave, 2016).…”
Section: Opportunities and Obstacles To Adopting It In The Aid Sectormentioning
confidence: 99%
“…(Soesilo et al, 2019(Soesilo et al, & 2016, and the use of UAV drones in humanitarian action is a rapidly emerging field (Dowson, 2018;Tasevski, 2018). Kalkman (2018) carried out exploratory research into humanitarian aid agencies' use of technologies during post-crisis rehabilitation and found that the use of IT had significantly increased in these areas. It was concluded that technology must not be treated as a neutral fix since it can leave political aftermath if used incorrectly (Raghad and Dave, 2016).…”
Section: Opportunities and Obstacles To Adopting It In The Aid Sectormentioning
confidence: 99%
“…His life is filled with meaning, although he does not always formulate it for himself. It is in constant development and contributes to the development of other people (Kalkman, 2018). Realizing that his life may not be entirely easy, he must learn to easily adapt to the rapidly changing conditions of life.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Debates about "experimental" technology are related to this issue. This links to the gap between laboratory and humanitarian field use, the effects and implications of using humanitarian technologies in volatile aid settings (Kalkman 2018), and how to limit risks, referring to revitalized discussions about the principle of "do no harm" (i.e. delivering aid without causing harm) in the context of humanitarian technology (Sandvik, Jacobsen and McDonald 2017).…”
Section: Technologymentioning
confidence: 99%